Urban dynamics and growth advances in urban economics - Capello, Roberta, 1962-; Nijkamp, Peter (Emerald, 2005)
The volume aims to produce an updated collection of advanced theories and methods in the field of urban policies, and highlights modern urban policies that stem from them. Contributions stress the limits of previous theories and methods, and emphasize the new directions that are developed in the field, and barriers that are overcome, providing in this way a dynamic perspective on theoretical and methodological knowledge in the field of urban economics. Urban policies, as well as practical problems envisaged in our modern cities, that take advantage from this theoretical development are stressed.
Includes index.
Keywords: Urban economics.; elektronické knihy; electronic books